Diagnostic Utility of Skin Prick Test Ratios and Specific IgE in Predicting Egg White Allergy: Reducing the Need for Oral Food Challenges in Children - Demir Sahin, Filiz; Kapcay, Ozan; Kilic, Mehmet; Sahin Sindi, Hilal (Mdpi, 2026)
Background: Skin prick testing (SPT) and serum egg white-specific IgE (sIgE) support oral food challenge (OFC) decisions in suspected egg allergy, but the incremental value of histamine-normalized SPT indices remains uncertain. Methods: In this single-center retrospective study, 105 egg-sensitized children underwent clinically indicated OFC. Commercial egg white SPT, prick-to-prick testing with fresh egg white, histamine controls, and serum egg white-specific IgE were assessed. Discriminatory performance was evaluated by ROC analysis, and independent predictors of OFC positivity were identified using multivariable logistic regression. Results: OFC was positive in 23 of 105 children (21.9%). Egg white SPT wheal diameter, the prick-to-histamine ratio, and serum egg white-specific IgE (sIgE) levels were significantly higher in OFC-positive patients (all p < 0.001). ROC analysis demonstrated moderate-to-good discrimination for both sIgE (AUC = 0.767) and the prick-to-histamine ratio (AUC = 0.786), without clear superiority of normalized indices. In multivariable logistic regression analysis, only absolute egg white SPT wheal diameter (adjusted OR 1.41 per 1 mm increase; 95% CI 1.13-1.77) and serum egg white-specific IgE level (adjusted OR 31.86 per 100 kUA/L increase; 95% CI 1.60-636.15) remained independent predictors of OFC positivity. Conclusions: Absolute egg white SPT wheal diameter and serum sIgE independently predict OFC outcomes in egg-sensitized children. Histamine-normalized indices did not provide added value over wheal size alone. These findings support a probabilistic, context-based use of test results to inform selective OFC planning rather than replace OFC.
Keywords: egg white allergy; oral food challenge; skin prick test; prick/histamine ratio; specific IgE